Correlation of anterior cerebral artery resistive index with early comorbidities in preterm neonates - Gill, Karambir Singh; Gupta, Bhavna; Pooni, Puneet A.; Bhargava, Siddharth (Frontiers in Pediatrics, 2024)
TITLE: Correlation of Anterior cerebral artery(ACA) Resistive Index (RI ) with early comorbidities in preterm neonates. INTRODUCTION: This study was undertaken to find the clinical correlation of RI in ACA of preterm neonates admitted to NICU with comorbidities such as perinatal asphyxia, neonatal sepsis, and necrotizing enterocolitis. METHODS: An observational analytical study including preterm neonates (<35 weeks) admitted to NICU. Ultrasound cranium was done on the D1-D3 and D7 of life as per study protocol. Baseline and clinical data of asphyxia, sepsis, and NEC were obtained. Images were obtained using a 4-8MHz probe of a Sonosite M-turbo machine. All statistical calculations were done using SPSS 21.0 version (SPSS Inc., Chicago, IL, USA )with the application of Kolmogorov-Smirnov test and the Mann-Whitney test. RESULTS: During the study period, a total of 739 neonates were admitted. Out of which, 73 neonates constituted the study group. Out of 73 patients, 33 were preterm neonates without comorbidities, and 40 neonates had other comorbidities such as perinatal asphyxia, sepsis, and NEC Stage 2 & 3 (Necrotizing enterocolitis). In the present study, the mean RI on day 3 of life was 0.76 ± 0.04 in babies without comorbidities and 0.77 ± 0.04 in neonates with comorbidities with a p-value of 0.247. On the 7th day of life, the mean RI was 0.82 ± 0.03 in both groups, with a p-value of 0.42. CONCLUSION: We could not find any significant clinical correlation of RI in ACA of preterm neonates less than 35 weeks of gestation with comorbidities. KEYWORDS: RI, ACA, Preterm, neonates, Doppler